2004
DOI: 10.1093/molehr/gah052
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of the human testis-specific serine/threonine kinase (TSSK) homologues. A TSSK member is present in the equatorial segment of human sperm

Abstract: Two members of the human testis-specific serine/threonine (Ser/Thr) kinase family, TSSK 1 and TSSK 2, were cloned and sequenced from a human testis adaptor-ligated cDNA library using a PCR strategy. Within the cDNA, open reading frames (ORF) were defined encoding proteins of 367 and 358 amino acids respectively, as well as conserved kinase domains typical of the superfamily of Ser/Thr kinases. Both genes were intronless and mapped to chromosomes 5 and 22 respectively. The human and mouse homologues of TSSK 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
101
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 36 publications
11
101
1
Order By: Relevance
“…Additionally, a group of genes that have generally been classified as ones involved in metabolism are significantly down-regulated in the testis upon loss of Taf7l and likely reflect both metabolic and spermatogenesis functions. These genes include the Tssk3 or Tsks testis-specific kinases (31,32), as well as Camk4, a protein kinase involved in phosphorylating protamines (33); Hk1 and GCK hexokinases involved in sperm glycolysis linked to motility (34); and Oaz3 (ornithine decarboxylase antizyme) that controls polyamines required for proper sperm formation (35,36) (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a group of genes that have generally been classified as ones involved in metabolism are significantly down-regulated in the testis upon loss of Taf7l and likely reflect both metabolic and spermatogenesis functions. These genes include the Tssk3 or Tsks testis-specific kinases (31,32), as well as Camk4, a protein kinase involved in phosphorylating protamines (33); Hk1 and GCK hexokinases involved in sperm glycolysis linked to motility (34); and Oaz3 (ornithine decarboxylase antizyme) that controls polyamines required for proper sperm formation (35,36) (Fig. 2D).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown a 65 kDa protein, TSKS is a substrate of TSSK2 [26]. TSKS localizes predominantly to the centrioles of human sperm, however, TSSK2 is localized to the sperm neck, mid-piece of sperm tail, and to the equatorial segment (personal communication from John C Herr).…”
Section: Discussionmentioning
confidence: 99%
“…Mouse TSSK1 is abundant in germ cells during meiotic metaphase [25], while mouse TSSK2 is localized in the cytoplasm of male germ cells at late stage of spermatogenesis, and also in the flagella, acrosomal region of mature sperm, which is consistent with SPAG16L localization. In human sperm, TSSK2 was found in the neck region, equatorial region and midpiece of the flagella [20,25,26]. It has been shown that TSKS is a substrate for both TSSK1 and TSSK2 [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Through phosphorylation of proteins, the testis-specific serine/threonine kinase (TSSK) family, which is expressed abundantly in the testis, is deeply involved in sperm differentiation, capacitation and fertilization [6][7][8][9][10][11]. Up to now, five members of this family have been identified, including TSSK1, TSSK2, TSSK3, TSSK4 and TSSK6.…”
Section: Introductionmentioning
confidence: 99%
“…TSSK6, also named small serine/threonine kinase, is expressed in elongating spermatids, and its coding gene, TSSK6, is mapped to 19p13.11, with only one exon encoding 273 amino acids [9,16]. A further study proposed that TSSK6 can phosphorylate histones H1, H2A, H2AX and H3, and can associate with heat shock protein HSP90 and HSC70 [16].…”
Section: Introductionmentioning
confidence: 99%